BIOMONITORING OF SEVOFLURANE EXPOSURE IN ANESTHESIOLOGIST - Firly Ratsmita; Muhammad Ilyas (Universitas Airlangga, 2021)
ABSTRACTSevoflurane is used by anesthetists for the induction and maintenance of general anesthesia. This causes the anesthetist to get daily exposures. This will be a potential hazard for exposed operating room personnel, especially anesthetists. The adverse health effects of sevoflurane as hepatotoxic, nephrotoxic and neurotoxic in the human body can be a risk for anaesthetists. Biological monitoring can be done by measuring the levels of sevoflurane and its metabolites or by looking at biomarkers for their effects on health effects. The aim of this study was to seek a literature review on the biomonitoring of sevoflurane exposure in anaesthetists. We searched the literature review using the PRISMA method in PubMed and Google scholar using the following keywords